Adenovirus 36 seropositivity is related to obesity risk, glycemic control, and leptin levels in Chilean subjects - Sapunar, Jorge; Fonseca, Luis; Molina, Víctor; Ortiz, Eugenia; Barra, Maria Ines; Reimer, Camila; Charles, Maria; Schneider, Constance; Ortiz, Manuel; Brito, Roberto; Manríquez, Víctor; Pavez, Monica; et al. (International Journal of Obesity, 2020)
Adenovirus 36 (Ad-36) has been associated to adiposity in animal and in vitro studies. Ad-36 seropositivity has also been reported to contribute to obesity risk in children and adult populations. We investigated the relationship of Ad-36 serology with obesity and metabolic parameters in a Chilean population. Clinical and anthropometric data were obtained and blood samples were drawn from 99 lean (BMI: 18.5-24.9 kg/m ) and 151 obese (BMI > 30 kg/m ) subjects. Laboratory tests included lipid profile as well as glucose, insulin, leptin, and adiponectin levels. Ad-36 seropositivity was evaluated in serum samples by enzyme-linked immunosorbent assay. Seroprevalence of Ad-36 was higher in the obese group (58%) than in lean controls (34%) demonstrating that individuals previously infected with Ad-36 have higher risk of obesity in the study population (OR: 2.67, 95%CI: 1.58-4.51, p < 0.001). Interestingly, Ad-36 was related to lower concentrations of triglycerides and VLDL cholesterol in lean subjects (p = 0.049) and lower leptin in obese individuals (p = 0.014). Previous Ad-36 infection was also related to lower glycemia, insulinemia, and HOMA-IR (p < 0.05) in obese subjects who were not under antidiabetic drugs. Our results provide evidence of the contribution of previous Ad-36 infection to an increased risk of obesity in adult Chilean population. Ad-36 seropositivity was also associated to lipid profile, glycemic control, and leptin levels in adult Chilean population.